Factors Related to Acute Respiratory Infection Prevention Behavior After the COVID-19 Pandemic in Urban Communities: The Integration of Protection Motivation Theory - Mariati, Lusia Henny; Krowa, Yuliana R. R. (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
Following the end of the COVID-19 pandemic status, the incidence of acute respiratory infections (ARIs) has increased, affecting not only children but also adolescents and adults. The Protection Motivation Theory (PMT) provides a framework for understanding how individuals engage in preventive behaviors against ARIs. This study aimed to examine the relationship between factors influencing preventive behavior against ARIs by integrating PMT, which includes threat appraisal and coping appraisal components. A cross-sectional research design was employed using an online questionnaire distributed to a randomly selected sample of 320 respondents. Data were analyzed using both bivariate and multivariate logistic regression methods. The multivariate analysis revealed that among the five assessed factors—perceived severity, perceived threat, self-efficacy, response efficacy, response cost, and behavioral intention—the most significant predictors were response efficacy (p = 0.002, OR = 3.439) and behavioral intention (p = 0.004, OR = 1.988). The findings indicate that individuals with higher response efficacy were 3.4 times more likely to engage in ARI prevention behavior, while those with stronger behavioral intentions were 1.9 times more likely to do so, compared to other influencing factors.